1997
DOI: 10.1021/jp970173j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of HCl Acid Ionization in Water:  Ab Initio Potential Energy Surfaces and Monte Carlo Simulations

Abstract: The acid ionization of HCl in water is examined via a combination of electronic structure calculations with ab initio molecular orbital methods and Monte Carlo computer simulations. The following key features are taken into account in the modeling:  the polarization of the electronic structure of the solute reaction system by the solvent, the quantum character of the proton nuclear motion, the solvent fluctuation and reorganization along with the solvent polarization effects on the proton potential, and a Grot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
338
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 308 publications
(369 citation statements)
references
References 76 publications
29
338
0
2
Order By: Relevance
“…reoriented 2 I frame , which is determined to be 10 ps from our 3 M simulations (Fig. 3B) and which agrees with the 9.6-to 10-ps fsIRS result (9,10).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…reoriented 2 I frame , which is determined to be 10 ps from our 3 M simulations (Fig. 3B) and which agrees with the 9.6-to 10-ps fsIRS result (9,10).…”
Section: Resultssupporting
confidence: 87%
“…NMR determines the reorientation component proportional to the salt concentration. Because of the librational component, this time integral is not 2 I , which is defined in terms of an exponential decay after a brief librational transient (15); it is instead from Eq. 7 (1 Ϫ C lib )/(1/ lib ϩ 1/ 2 I ) ϩ C lib 2 I , which is 1.5 ps in the 1 M solution from our model (see Table 1), in reasonable agreement with the experimental 1.7 (13) to 2.3 (12) ps value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23) To confirm the generality of the simulated dynamics, we introduced a second hydronium ion and restarted the MD run for approximately 2 ps. We found that a similar hydrogen-bonded hydronium ion is again formed, which plays the same role as that prior to the Volmer step.…”
Section: Volmer Step: Hydrogen Adsorptionmentioning
confidence: 99%
“…The key issue had to do with the molecular-level mechanism of the heterogeneous HCl + ClONO 2 → Cl 2 + HNO 3 reaction of hydrochloric acid with chlorine nitrate that Susan Solomon (136) had proposed as the culprit for ultimately producing ozone-destroying chlorine. With (now) postdoc Gertner, we proposed a way for HCl-our old friend from our solution PT work (110,111)-to acid dissociate at the surfaces of polar stratospheric cloud ice particles (137,138). As for the net Cl 2 -producing reaction itself, one suggestion was that it occurred in two steps, the first being the hydrolysis of chlorine nitrate, ClONO 2 + H 2 O → HOCl + HNO 3 , followed by HCl+ HOCl → H 2 O + Cl 2 .…”
Section: Atmospheric Interstellar Biological and Renewable Energy mentioning
confidence: 99%